2011
DOI: 10.3146/ps11-5.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Seed Treatment Effects in Organic Peanut

Abstract: Stand establishment has been a challenge for organic peanut production in the Southeastern United States. Field experiments were conducted in 2007 and 2009 in research plots certified for organic production to evaluate the potential of genotype selection, shelling procedure, and seed treatment with Bacillus subtilis to improve stand establishment and seedling emergence rates, reduce incidence of Aspergillus crown rot, and increase seedling biomass. Seed of 15 peanut genotypes were mechanically shelled or hand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…4 and 5), although final totals of both stand counts and dead plants were equal to the untreated in all three field experiments (including the Blackshank location in 2010 -data not shown). Other studies have suggested that B. subtilis has the potential to aid in germination and emergence for improved stand establishment (Cantonwine et al, 2011;Ruark and Shew, 2010;Turner and Backman, 1991). The most favorable responses to B. subtilis have been under stressed conditions, such as seed that were mechanically shelled (Cantonwine et al, 2011), or unfavorable planting conditions from limited water, poor rotation, or cool soils (Turner and Backman, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4 and 5), although final totals of both stand counts and dead plants were equal to the untreated in all three field experiments (including the Blackshank location in 2010 -data not shown). Other studies have suggested that B. subtilis has the potential to aid in germination and emergence for improved stand establishment (Cantonwine et al, 2011;Ruark and Shew, 2010;Turner and Backman, 1991). The most favorable responses to B. subtilis have been under stressed conditions, such as seed that were mechanically shelled (Cantonwine et al, 2011), or unfavorable planting conditions from limited water, poor rotation, or cool soils (Turner and Backman, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have suggested that B. subtilis has the potential to aid in germination and emergence for improved stand establishment (Cantonwine et al, 2011;Ruark and Shew, 2010;Turner and Backman, 1991). The most favorable responses to B. subtilis have been under stressed conditions, such as seed that were mechanically shelled (Cantonwine et al, 2011), or unfavorable planting conditions from limited water, poor rotation, or cool soils (Turner and Backman, 1991). Yet, in the previous research from South Georgia, only one out of 15 genotypes in each year of the trial had a positive plant stand response that was solely related to B. subtilis seed treatment (Cantonwine et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, certified organic peanut production is limited to the southwestern region of the United States (Guerena & Adam, 2008); however, research continues to be conducted to facilitate the successful production of organic peanut in the southeastern region of the United States. Alternative products and methods for seed treatment and weed control have been the main focus of this effort (Cantonwine, Holbrook, Culbreath, Tubbs, & Boudreau, 2011; Johnson, 2019). Lack of postharvest infrastructure is also a challenge for farmers in the southeastern region of the United States.…”
Section: Question 1 Would You Be Interested In Growing Peanuts Organmentioning
confidence: 99%